Caracterização morfológica, molecular e reação de acessos de melancia a Didymella bryoniae - Medeiros, Ravier Valcácer de (2015)
The aim of this study was to characterize morphologically and molecularly 24 watermelon accessions belonging to the Cucurbitaceae Germplasm Collection of Plant Genetic Resources Laboratory at the Federal Rural University of the Semi-Arid (UFERSA) and promote the selection of sources of resistance among these accesses gummy. For the morphological characterization were used watermelon 24 hits and two commercial cultivars as witnesses, Crimson Sweet and Olympia. The design was a randomized complete block design with three replications and five plants per plot. The characterization was performed using morphological and agronomic descriptors only in fruit characters. We conducted analysis of variance and clustering of means by Scott-Knott at 5% probability test With these data were obtained generalized Mahalanobis distances (D2ij) and access grouped by the method based on the average linkage (UPGMA) with tailoring dendogram and evaluation of the relative contribution of descriptors for genetic divergence. Molecular characterization was performed using RAPD markers. The products of the amplifications were counted as absence of allele (0) and presence of the allele (1). The estimate of genetic similarity between each pair of genotypes was calculated by Sorence-Dice coefficient. One hundred primers SSR that were developed for melons were evaluated for their transferability watermelon. To observe the reaction of access to D. bryoniae the design was completely randomized with three repetitions and the same genotypes used in the characterization. Each plot consisted of five plants. Inoculation was accomplished in seedlings 25 days after planting, with the inclusion of colonized with toothpicks isolated on the lap of the seedlings, and to witness sticks sterilized without presence of inoculum. The evaluations were initiated seven days after inoculation and thereafter, performed every seven days for three weeks. Disease severity was assessed by using a grade scale ranging from 0 to 4, taking to review the notes for the last valuation date. The average data of notes per plot were subjected to analysis of variance (ANOVA) and averages grouped by Scott and Knott test at 5% probability. Observed significant results for the bulk of the fruit descriptors (MF), length (L) and width of fruit (L), fruit shape (FF), shell thickness in the stalk region (EC1), soluble solids (SS), color pulp (CP), pattern of stripes (PL) and external fruit color (CF). The grouping of hits from the morphological descriptors produced as only three access groups. Since the descriptors that most contributed to genetic divergence were L, FF, MF, PL, SS, C, CF and CP with 19:12%, 13:56%, 11:53%, 19.10%, 9.80% 8:37%, 7.83% and 5.22% respectively. The clustering performed with molecular markers produced five groups. In the analyzes of transferability 77% of SSR primers showed promise for use in work with watermelon. For reaction to D. bryoniae there was a significant effect of these hits, highlighting A-1, A-6, A-10, A-11, A-14 with resistance. Promising for future steps in breeding programs. Thus, it can be said that there are morphological and molecular differences in accessions, as well as possible sources of resistance to D. bryoniae